2007
DOI: 10.1038/sj.ejcn.1602652
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an increased intake of vegetables and fruit on weight loss, blood pressure and antioxidant defense in subjects with sleep related breathing disorders

Abstract: Objective: To assess the effect of an increased consumption of vegetables and fruit on body weight, risk factors for cardiovascular disease (CVD) and antioxidant defense in obese patients with sleep-related breathing disorders (SRBD). Design: Randomized, controlled trial of an intervention to increase the intake of vegetables to 400 g/day and fruit to 300 g/day. Dietary intake was calculated from a food frequency questionnaire. Antioxidant status was assessed with the ferric-reducing/ antioxidant power (FRAP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 36 publications
2
41
0
2
Order By: Relevance
“…The majority of energy/ fat intakes did not correlate with changes in body weight in the studies reporting on these findings, with some studies acknowledging that underreporting was likely (Cox et al, 1998;Maskarinec et al1999). Only one study by Svendsen et al (2007) showed consistent results with significant decreases in body weight alongside significant decreases in fat intake. Furthermore it is probable that accuracy of reporting is not the only limitation of dietary data collection but the likelihood that keeping a record of dietary intakes may also influence choices and therefore alter usual intakes (Djuric et al, 2006).…”
Section: Strengths and Limitationsmentioning
confidence: 59%
See 3 more Smart Citations
“…The majority of energy/ fat intakes did not correlate with changes in body weight in the studies reporting on these findings, with some studies acknowledging that underreporting was likely (Cox et al, 1998;Maskarinec et al1999). Only one study by Svendsen et al (2007) showed consistent results with significant decreases in body weight alongside significant decreases in fat intake. Furthermore it is probable that accuracy of reporting is not the only limitation of dietary data collection but the likelihood that keeping a record of dietary intakes may also influence choices and therefore alter usual intakes (Djuric et al, 2006).…”
Section: Strengths and Limitationsmentioning
confidence: 59%
“…Furthermore the study by Cox et al (1998) showed significant increases in body weight alongside a nonsignificant decrease in both energy (-24 kcals) and fat (-3%) intakes. Svendsen et al (2007) found significant decreases in body weight together with significant decreases in fat intakes of -4% and non-significant decreases in energy intake (-213 kcals). Two studies by Watzl et al (2005) and Whybrow et al (2006) showed neither significant change in body weight or energy/ fat intakes.…”
Section: Analysis Of Findings For Systematic Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…Other intervention studies have found an effect of increased fruit intake on total energy intake (23)(24)(25)(26)(27) . These intervention studies are either behavioural intervention studies, addressing several dietary and lifestyle factors among free-living individuals (24)(25)(26) , or clinical trials, implementing strict dietary regulations (23,27) . Common to all these studies is that participants were either overweight or obese and may thus have had a high motivation for weight reduction.…”
Section: Discussionmentioning
confidence: 99%